Tobacco science, policy and public health - Boyle, P. (Peter) (Oxford : Oxford University Press, 2010)
Tobacco is ranked as one of the major public health disasters of modern times. This title pulls together the science of tobacco-related diseases with the policy of tobacco control to offer a comprehensive preventive medicine/public health approach.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Tobacco -- Physiological effect; Nicotine addiction -- Treatment; Tobacco use -- Health aspects; Tobacco use -- Government policy